Eternal-Thing 3.0: Mixed-Mode SoC for Energy Harvesting System Towards Sustainable IoT - Saswat Kumar Ram; Sanjeev Mani Yadav; Jayendra Kumar; Priyanka Singh; Banee Bandana Das (IEEE Access)
The power requirement in IoT is essential to fulfill the energy demand of the power-hungry sensors at end nodes. The use of fixed batteries restricts sustainability and makes the system costly. This work presents a battery-less solar energy harvesting system (EHS). Designing a state-of-the-art EHS needs a lot of exercise. Proper modeling of each unit makes the system robust and can be tuned at every stage to get an optimum result. The proposed EHS comprises a clock generator, DC-DC converters, analog-to-digital converters (ADCs), a maximum power point tracking (MPPT) unit, and a digital controller. The DC-DC converter and ADCs are designed in Verilog-A. The MPPT module digital controller is designed using Verilog HDL. The digital controller decides the mode of operation of the EHS based on power availability. Verilog-AMS allows us to do the mixed-mode simulation very early, so errors can only be eliminated in the initial stages at the circuit level. The proposed EHS is simulated in the Cadence Virtuoso AMS Designer Simulator (using the Incisive Run tool). The input solar voltage is 1 V to 1.5 V, and the output is 3 V to 3.5 V. The EHS provides supply voltages of 3.3 V, 1.8 V, and 1 V to the end node devices in IoT. The EHS is further designed with the parameters obtained from modeling in Cadence using virtuoso (for analog circuits) and genus (for digital circuits) and finally combined in Innovous (mixed-mode tool) for tape-out.